Kegiatan Penapisan Kadar Hemoglobin untuk Mencegah Kejadian Anemia pada Populasi Lanjut Usia di Gereja St. Fransiskus Asisi - Wijaya, Christian; Setia, Nicholas; Alvianto, Fidelia; Kurniawan, Joshua; Nathaniel, Fernando; Santoso, Alexander Halim (Jurnal Suara Pengabdian 45, 2024)
The World Health Organisation (WHO) estimates that the global population aged over 60 years will increase from 900 million in 2015 to 2 billion in 2050. This demographic is particularly vulnerable to disease and disability, with declining haemoglobin levels long considered a consequence of aging. Nutritional deficiencies, chronic diseases, kidney disease, haematological malignancies, and anemia of unknown cause can all contribute to anemia in the elderly. This significantly impacts physical performance, cognitive function, and overall health. We carried out this activity at St. Francis Assisi, Jakarta, with 36 participants. We perform a physical examination and a complete blood count, including haemoglobin and hematocrit levels, to detect nemia. Among the 36 participants, 18 people (50%) had mild anaemia, 6 people (16.7%) had moderate anaemia, and 1 person (2.8%) had very severe anaemia. Anaemia in the elderly can cause severe health consequences, including physical and cognitive decline, increased hospitalisations, and death. Routine screening for haemoglobin and hematocrit levels is essential for early detection and intervention, improving quality of life and health outcomes for older adults.